1999
DOI: 10.1192/bjp.175.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological function in euthymic patients with bipolar disorder

Abstract: These findings provide good evidence for the existence of neuropsychological impairment in patients with euthymic bipolar disorder, although the possible effect of medication should not be overlooked. This may be of clinical relevance and raises questions about the course and outcome of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
342
6
38

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(418 citation statements)
references
References 24 publications
32
342
6
38
Order By: Relevance
“…Cognitive impairments have previously been described in FH and also in manic, depressed, and euthymic BD patients (Sobczak et al, 2002c;Rossi et al, 2000;Martinez-Aran et al, 2000;Ferrier et al, 1999;Murphy et al, 1999;Rubinsztein et al, 2000). The cognitive deficits in BD may be partially explained by abnormalities in functional brain structures and/or metabolism (Stoll et al, 2000;Manji et al, 2000;van Gorp et al, 1999;Coffman et al, 1990).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Cognitive impairments have previously been described in FH and also in manic, depressed, and euthymic BD patients (Sobczak et al, 2002c;Rossi et al, 2000;Martinez-Aran et al, 2000;Ferrier et al, 1999;Murphy et al, 1999;Rubinsztein et al, 2000). The cognitive deficits in BD may be partially explained by abnormalities in functional brain structures and/or metabolism (Stoll et al, 2000;Manji et al, 2000;van Gorp et al, 1999;Coffman et al, 1990).…”
Section: Discussionmentioning
confidence: 89%
“…The cognitive deficits in BD may be partially explained by abnormalities in functional brain structures and/or metabolism (Stoll et al, 2000;Manji et al, 2000;van Gorp et al, 1999;Coffman et al, 1990). As cognitive impairments are present in FH and persist during clinical remission in BD patients, they may be regarded as trait markers (Henry et al, 1973;van Gorp et al, 1998;Murphy et al, 1999;Coffman et al, 1990;Ferrier et al, 1999;Rubinsztein et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of studies have now confirmed that many patients with BD have cognitive impairment that persists into the euthymic state. [154][155][156][157][158][159] Impairment has been demonstrated in sustained attention, 160 working memory and executive function, 155 global cognitive functioning, 154 visuospatial recognition memory, 161 problem-solving strategies, 156 declarative memory, 157 and cognitive processing speed. 162 The fact that such impairment is detectable independent of clinical state is suggestive of a trait marker, but factors such as the neuropsychological deterioration secondary to acute episodes of illness, medication treatment, and/or withdrawal effects, long-term effects of comorbid conditions such as substance abuse, or the effect of unrecognized neurobiological changes such as dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis could all contribute to performance deficits in the euthymic state.…”
Section: Cognitive Endophenotypesmentioning
confidence: 99%
“…Although the illness is defined by the occurrence of mania, the depressed phase predominates (Judd et al, 2002(Judd et al, , 2003 and represents the greatest therapeutic challenge. Pronounced neurocognitive dysfunction is also frequently described in symptomatic bipolar patients and there is increasing evidence of specific impairments which may persist in euthymia and therefore represent a relatively enduring abnormality (Ferrier et al, 1999;Ferrier and Thompson, 2002;Thompson et al, 2000). It has been suggested that abnormalities in hypothalamic-pituitaryadrenal (HPA) axis function may cause or exacerbate both neurocognitive impairment and depressive symptoms (McQuade and Young, 2000;Sapolsky, 2000).…”
Section: Introductionmentioning
confidence: 99%